2007
DOI: 10.1002/ppap.200600087
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Barrier Discharge at Atmospheric Pressure as a Tool to Deposit Versatile Organic Coatings at Moderate Power Input

Abstract: Plasma coating technologies have been demonstrated as being promising for the fabrication of bioactive and biocompatible materials, among others. Reported efforts are exclusively focused on the two‐step approaches, in which the bioactive component is first immobilized on a substrate, followed by a (vacuum) plasma polymerization treatment or vice versa. However, we believe that upon minimizing the plasma energy, numerous bioactive substances such as enzymes and nucleic acids can be immobilized directly in plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
65
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(70 citation statements)
references
References 58 publications
4
65
0
1
Order By: Relevance
“…It has been reliably demonstrated that ppAAc surfaces can be prepared to be stable for up to 300 days, 47 and with regards to scale-up, vacuum pressure technology is now widespread for preparing coatings in industry. 48 …”
Section: Discussionmentioning
confidence: 99%
“…It has been reliably demonstrated that ppAAc surfaces can be prepared to be stable for up to 300 days, 47 and with regards to scale-up, vacuum pressure technology is now widespread for preparing coatings in industry. 48 …”
Section: Discussionmentioning
confidence: 99%
“…The fact that the polymerization process can be performed at atmospheric conditions highlights its simplicity. [26,27] In order to get an insight in the modifications made to the surface, a varied set of surface analysis techniques are used. Hence, for both plasma methods, static water contact angle goniometry (WCA), Fourier transform infrared spectroscopy (FT-IR), X-ray photoelectron spectroscopy (XPS), atomic force microscopy (AFM) and optical reflectance spectroscopy (OPS) are performed.…”
Section: Introductionmentioning
confidence: 99%
“…Their results suggest that Ar/O 2 and NH 3 /C 2 H 4 plasmas as potentially useful tools for bone tissue regeneration procedures. The use of the dielectric barrier dischargeprocess (DBD) to generate a reactive cold plasma to modify the surface chemistry of synthetic a natural materials has been explored by several groups [24,25]. It is characterized by relatively low engineering costs, high speed, and simplicity compared to lowpressure (vacuum) plasma techniques.…”
mentioning
confidence: 99%
“…The surface functionalization can be carried out in one step and several functional groups, e.g. OH, COOH, NH 2 , CNH, can be grafted on polymer surface depending on monomer selected [21][22][23][24][25]. de Valence et al [26] studied the effect of cold air plasma treatment on the hydrophilicity of electrospun polycaprolactone scaffolds in order to improve cell-material interactions and promote better tissue regeneration for biodegradable vascular graft applications.…”
mentioning
confidence: 99%